Biosorption of diethylketone and Cd using a Streptococcus equisimilis biofilm supported on vermiculite: kinetics and equilibrium studies - Costa, Filomena Cristina Pinto (2015)
WMESS 2015 - The World Multidisciplinary Earth Sciences Symposium